Triglyceride glucose index - body mass index predicts insulin resistance, metabolic syndrome and associates with impaired ovulation in Chinese women with polycystic ovary syndrome - Guan, Muxin; Feng, Jiaxing; Zhu, Mengyi; Wang, Yu; Shi, Baichao; Lu, Fengjuan; Yu, Jiannan; Gao, Zhuwei; Yu, Hong; Wu, Xiaoke (Frontiers in Endocrinology, 2025)
BackgroundInsulin resistance (IR) and metabolic syndrome (MetS) are highly prevalent and pathophysiologically central features of polycystic ovary syndrome (PCOS). However, their assessment is challenged by the limitations of gold-standard diagnostic methods. The clinical utility of the novel triglyceride glucose index - body mass index (TyG-BMI) for predicting IR, MetS, and its association with fertility outcomes in Chinese women with PCOS remains unexplored and warrants investigation.ObjectiveTo evaluate the association between TyG-BMI and IR and MetS, and fertility outcomes in women with PCOS.MethodsWe used data of 855 participants of the Acupuncture and Clomiphene for Chinese Women with Polycystic Ovary Syndrome (PCOSAct) trial. Linear trend tests and logistic regression evaluated relationships between TyG-BMI and anthropometric, hormonal, metabolic, and fertility outcomes. Receiver operating characteristic (ROC) curves assessed TyG-BMI’s predictive value for IR and MetS. RCS analysis was used to examine threshold effects between TyG-BMI and IR, MetS, and ovulation. A likelihood ratio test was further incorporated to validate the model fit.ResultsTyG-BMI was positively association with IR (OR: 2.747, 95% CI: 1.942–3.887) and MetS (OR: 4.176, 95% CI: 2.278–7.653). TyG-BMI had a strong predictive performance, with AUCIR of 0.841 and AUCMetS of 0.899. For fertility outcomes, after adjusting for confounders, only ovulation showed a significant negative association (OR: 0.984, 95% CI: 0.973–0.994). The study revealed significant nonlinear associations between TyG-BMI and both IR and MetS, but a linear link with ovulation status. The inflection point occurred at a TyG-BMI of 203. Below this, IR risk increased progressively with TyG-BMI, plateauing above it. Above 203, MetS prevalence continued to increase, while ovulation rates declined inversely.ConclusionElevated TyG-BMI is strongly associated with worsened IR and MetS in PCOS women, serving as a practical screening tool for these conditions, while also demonstrating a potential negative impact on ovulation.